1976
DOI: 10.1002/jhet.5570130627
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic studies of the antitumor antibiotic streptonigrin. II. Synthesis of the C‐D ring portion of streptonigrin

Abstract: Partial mclhylalion of gallopropiophenonc (4) followed by benzylation and base‐catalyzed condensation with ethyl acetate yielded 3‐(2‐benzyloxy‐3,4‐din]etlK>xy)benzoyl‐2‐butanonc (6). Animation of the latter and subsequent base‐catalyzed cyclization with ethyl cyanoacetate gave 4‐(2‐benzyloxy‐3,4‐dimethoxy)phenyl‐5,6‐dimethyl‐2‐oxo‐1,2‐dihydropyridine (8). Removal of the 2‐oxo group of 8 through chlorination and dechlorination and stepwise conversion of the 5‐cyano and 2‐methyl groups into the 5‐amino and 2‐ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Wittek, and Cheng (see also Scheme 7), 73 was condensed with methyl acetoacetate to form the 3-acetyl-4-arylpyridone 195. The acetyl group was reduced to the alcohol 196 (possibly a diastereomeric mixture, due to the presence of both central and axial chirality, but not specified) and further converted to the 2-chloro-3-vinylpyridine 197 by using phenylphosphoryl dichloride.…”
Section: Kende's Approachmentioning
confidence: 99%
“…Wittek, and Cheng (see also Scheme 7), 73 was condensed with methyl acetoacetate to form the 3-acetyl-4-arylpyridone 195. The acetyl group was reduced to the alcohol 196 (possibly a diastereomeric mixture, due to the presence of both central and axial chirality, but not specified) and further converted to the 2-chloro-3-vinylpyridine 197 by using phenylphosphoryl dichloride.…”
Section: Kende's Approachmentioning
confidence: 99%
“…The synthesis of substituted 5H-chromeno[3,4-c]pyridin-5-ones has been studied by many workers and various methods have been reported for the preparation of these compounds, including the condensation of 3-cyano-4-(2-hydroxyphenyl)pyridine derivatives in PPA or HBr/HCl [11][12][13][14], of 4-(2-fluorophenyl)nicotinic acid upon heating [15], of salicylaldehyde, malononitrile, or ethyl cyanoacetate and ketones in the presence of ammonium acetate [16][17][18][19][20][21], of 4-dicyanomethylene-4H-1-benzopyrans with amines [22], and of 3-acetylcoumarin with cyanoacetamide and ketones [23].…”
mentioning
confidence: 99%
“…A rapid reaction occurred affording [Fe2(CO)4(775-C5H5)2] together with a purple crystalline dimolybdenum complex 2. ['H NMR (C6D6) r 4.91 (s, 5 H, C5H5), 6.20 (s, 5 H, C5H5), 7.60 (s, 6 H, Me), 7.75 (s, 6 18.4 (Me)]. Elemental analyses and mass spectroscopy indicated that 2 had the molecular formula [Mo2(MeC2Me)4-(ij5-C5H5)2] in agreement with the NMR data.…”
mentioning
confidence: 99%
“…For our initial studies the protonation reaction was chosen. Treatment of 2 with an excess of anhydrous trifluoroacetic acid at 0 °C led to a rapid reaction and the formation of the purple crystalline salt [Mo2- (4), Mo(l)-C(3) = 2.317 (4), Mo(2)-C(4) = 2.240 (4), Mo(2)-C(5) = 2.287 (4), Mo(l)-C(6) = 2.341 (5), Mo(l)-C(7) = 2.321 (4), Mo-(1)-C(8) = 2.233 (4), C(l)-C(2) = 1.426 (5), C(2)-C(3) = 1.414 (6), C(3)-C(4) = 1.499 (5), C(4)-C(5) = 1.429 (7), C(5)-C(6) = 1.524 ( 6), C(6)-C(7) = 1.412 (6), C(7)-C(8) = 1.435 (7) A. 3 Hz), 7.87 (s, 3 H, Me), 7.96 (s, 3 H, Me), 9.03 (d, 3 H, Me, /hh = 2 Hz), 9.06 (s, 3 H, Me), 19.37 (m, 1 H, MoHC)].…”
mentioning
confidence: 99%